Time-and-ID-Based Proxy Reencryption Scheme - Kambombo Mtonga; Anand Paul; Seungmin Rho (Journal of Applied Mathematics)
Time- and ID-based proxy reencryption scheme is proposed in this paper in which a type-based proxy reencryption enables the delegator to implement fine-grained policies with one key pair without any additional trust on the proxy. However, in some applications, the time within which the data was sampled or collected is very critical. In such applications, for example, healthcare and criminal investigations, the delegatee may be interested in only some of the messages with some types sampled within some time bound instead of the entire subset. Hence, in order to carter for such situations, in this paper, we propose a time-and-identity-based proxy reencryption scheme that takes into account the time within which the data was collected as a factor to consider when categorizing data in addition to its type. Our scheme is based on Boneh and Boyen identity-based scheme (BB-IBE) and Matsuo’s proxy reencryption scheme for identity-based encryption (IBE to IBE). We prove that our scheme is semantically secure in the standard model.